Environmental Accounting System Model in the Era Artificial Intelligence and Blockchain Technology: A Bibliometric Analysis - Jannah, Richatul; Sari, Maylia Pramono; Utaminingsih, Nanik Sri; Halimah, W. N.; Pradana, P. T.; Rahmawati, D. A. (Economic Education Analysis Journal, 2023)
Environmental accounting in the era artificial intelligence and blockchain technology is also being considered as a new direction. Artificial intelligence and blockchain technology have revolutionized how organizations carry out transactions and store information. This research aims to describe publication activity evolution, broaden the knowledge, identify the most representative authors and journals, and offer insight into potential new directions, especially regarding environmental accounting system model in the era artificial intelligence and blockchain technology. This research follows a process of systematic literature review. The publications used in this study are from 2009 to 2023. The data used in this study came from 77 sources in the form of 27 articles, 7 book chapters, 24 conference papers, 5 conference reviews, 13 editorials, and 1 short survey from 2018 to 2023. Network visualization result shows research related to the influence of these technologies has not been done much and works analyzing these influences are scarce especially about environmental accounting model recently. The findings of this study serve as a reference and provide direction for future researchers and provide mapping related to environmental accounting system model in the era artificial intelligence and blockchain technology. More research on the influence of these technologies are needed.